Motion Picture Paradise : A History of Florida's Film and Television Industry. - Morton, David (Gainesville : University Press of Florida, 2024)
This book is a sweeping story of filmmaking in Florida, chronicling the state's importance to producers throughout 125 years by looking at the many iconic films and television shows made across the peninsula.
N -- O -- P -- R -- S -- T -- W -- About the Autor
Description based upon print version of record.
JSTOR
Keywords: Motion picture locations -- Florida -- History; Motion picture industry -- Florida -- History; Florida -- In motion pictures; Extérieurs (Cinéma) -- Floride -- Histoire; Cinéma -- Industrie -- Floride -- Histoire; SOCIAL SCIENCE / Media Studies; HISTORY / United States / State & Local / South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); Motion pictures; Motion picture locations; Motion picture industry; Florida; Media, entertainment, information & communication industries; Media Studies; History